Citizens' perceptions of the health-related neighbourhood environment in Limassol, Cyprus. (13th November 2019) - Kleopa, D; Panayiotou, A; Kouta, C; Middleton, N
Abstract: Background: "Place" can impact on health and quality of life. There is a growing interest in neighbourhood audits. In the context of developing the CyNOTes audit tool, a residents' perception of the neighbourhood environment survey was performed. Methods: A systematic random sample of ten adult residents (N = 150) across a stratified sample of fifteen neighbourhoods according to educational attainment as per census data responded to the "Place Standard" tool which assesses 14 aspects of the physical, built and social neighbourhood environment. Neighbourhoods were also audited using the 126-item CyNOTes. Results: Three in four participants were home owners and lived in the neighbourhood for over 10 years. With the exception of "identity and sense of belonging" (M = 5.8, SD = 2.0) and "opportunities for social interaction" (M = 5.3, SD = 2.1), physical and built aspects of the environment were rated close to the middle point on a scale 1: large to 7: little room for improvement. "Parks, playgrounds and green space" and "garbage, animal droppings and other physical disorder" were the most commonly mentioned priorities for action in the free text by one in three participants. The lowest score was recorded for "influence and sense of control" (M = 3.4, SD = 2.4). While on a 1-10 subjective perception of neighbourhood position, residents in lower education neighbourhoods gave a rating of 6.6 on average compared to 8.1 in the higher group, they tended to rate aspects of their neighbourhood more favourably. Even though the audit revealed a systematic pattern of less favourable conditions along the socio-economic continuum, the perception survey revealed a U-pattern with residents in the middle category more likely to give less favourable ratings. Conclusions: The extent to which perceptions surveys may be affected by differential expectations across social groups is not clear. Neighborhood audits provide supplementary profiles of "place" independent of the perceptions of residents. Key messages: Based on the Place Standard tool, Limassol residents' rate social aspects of their neighbourhood environment more favourably than aspects of the built and physical environment. Neighbourhood observed-based audits, independent of residents' perceptions surveys can supplement each other in city health profiling.